The Barmer study: impact of standardized warming of the injection site to enhance insulin absorption and reduce prandial insulin requirements and hypoglycemia in obese patients with diabetes mellitus. (May 2014) - Pfützner, A.; Hermanns, N.; Funke, K.; Forst, T.; Behnke, T.; Bitton, G.; Nagar, R.; Raz, I.; Haak, T.
Abstract Background: The primary objective of this prospective controlled study was to investigate the impact of standardized injection-site warming on prandial rapid acting insulin dose and glycemic control when studied under real-world conditions. Methods: All 145 participating patients (51 female, 94 male, 13 type 1 and 132 type 2 patients, age: 61.6 ± 8.4 yrs, HbA1c: 7.19 ± 0.50%) were treated with intensive insulin glargine and short-acting insulin analog therapy. After a 4 week treatment optimization run-in period, patients were randomized to continue therapy for three months without (control) or with a local injection-site warming device (InsuPad*). Observation parameters included HbA1c, insulin dose, frequency of hypoglycemia, body weight and adverse events. Results: HbA1c improved in both arms until study end (control group: 6.3 ± 0.5%; injection-site warming device: 6.3 ± 0.5%; both p < 0.001 vs. baseline). To achieve this good control, patients in the control group needed to increase the daily prandial insulin dose by 8.1% (from 66 ± 31 U to 71 ± 38 U, p < 0.05) with stable basal insulin requirements. Patients who used the injection-site warming device required less prandial insulin (70 ± 43 U to 55 ± 34 U; −19%, p < 0.001) and slightly more basal insulin (+3.9%). Total daily insulin dose increased in the control group (+3.7%) and decreased with warming device use (−8.6%, p < 0.001). The number of hypoglycemic events (<63 mg/dL) during the observation period was higher in the control group (6.2 ± 9.9/patient vs. injection-site warming device: 3.3 ± 4.8/patient, p < 0.05). Main study limitations can be seen in the open label design reliability of the collected dose information and the very obese patient cohort. Conclusion: When treating obese patients to target with insulin therapy, use of an injection-site warming device for 3 months resulted in a lower frequency of hypoglycemic events and a reduction in prandial insulin analog requirements. If these results are confirmed in other patient populations, an injection-site warming device may be useful in achieving treatment targets with a safer and more efficient basal bolus therapy in insulin-treated patients with type 1 and type 2 diabetes.